(3gQOhJ jJMOK Yf eUQs - (3gQOhJs; (3NaGLI, eMeO UbQs ((3GdbGgQIs (3GdeQcR Gdbhej ddJQLeIs, 2007)
(3JMOK ajg (B" (3CHh GdJGQjN (B" (3Yf eUQ HYO RjGQJg dgG bHd GdejdGO HfMh NeSI bQhf (B.. (3CMGOjK jbQQ ai eWdYgG CfgG SJWhd (B" (3fXQkG deG JMed CQVgG ef YLGFH GdeNdhbGJ h ef GdHOGFY h GdQhGFY ai SGFQ Gdafhf h GdUfGYGJ (B" .. (3h jSJWQO djWdY GdOfjG Ydi UhQ GdMjGI GdeTQbI GdhVGAI GdJi YGTgG CSdGafG Ydi VaGa Gdfjd (B.. (3h dG jOY aQUI JeQ (B- (3h gh jYQV eG SeY h QCi (B- (3Ohf Cf jYHQ Yf EYLGHg GdTOjO HGdeUQjjf h Ohf Cf jTjO HJahbge h YXeJge h SHbge ai ejGOjf GdYdhe h GdeYGQa , h Ohf Cf jeJOM aVGFdge h jSJQjM Edi JbhGge h fRGgJge , h jKHJ dge GdaVd ai GdcTa Yf cKjQ ef GdYdhe h GdeYGQa GdJi CaGOJ efgG GdEfSGfjI YGeI h CaGO efgG bheg GdEZQjb NGUIs
12
Keywords: (3GdMVGQI GdaQYhfjIs; (3GdaQGYfIs; (3eUQ GdbOjeIs -- (3JGQjNs